The Cambridge handbook of labor in competition law - Paul, Sanjukta, 1976-; McGaughey, Ewan; McCrystal, Shae (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
As scholars and policymakers around the world seek a systematic approach to the question of 'gig work,' one of its regulatory dimensions - the intersection of labor and competition law - points toward a deeper reconceptualization of the conventional legal and economic categories typically brought to bear upon it. A comparative approach to the question of gig work further reveals the variety and contingency of background assumptions that are often overlooked in the context of domestic policy debates. By combining a detailed comparative doctrinal survey of the regulation of non-employee workers in domestic competition law systems with a set of essays reframing the underlying questions raised - in terms of international legal frameworks, freedom of association norms, alternative approaches to law and economics, and more - The Cambridge Handbook of Labor in Competition Law moves the debates over the fissured workplace and the labor - competition law intersection forward in novel ways.
'Labor in competition : introduction', Sanjukta Paul -- 'Collective Labour Rights for working people : the legal framework established by the International Labour Organization', Tonia Novitz -- 'Economic coordination as freedom of association', Alan Bogg -- 'The state's power to govern in this filed is paramount : antitrust, labor and the First Amendment', Charlotte Garden -- 'Competition Law as Collective Bargaining Law', Nathan Tankus and Luke Herrine -- 'Antitrust, free trade and fissuring', Erik Peinert -- 'American antitrust exceptionalism', Sanjukta Paul and Sandeep Vaheesan -- 'Competition and Labour Law in Canada : the contestable margins of legal toleration', Eric Tucker -- 'Workers and Competition Law in Japan', Masako Wakui -- 'Workers and Competition Law in Australia : the public benefits of collective bargaining', Shae McCrystal -- 'Workers and Competition Law in New Zealand', Dawn Duncan --- 'Competition Law and Labour Law : South Africa', DMDavis -- 'Workers and Competition Law in India : workers' associations are mostly not cartels', Supriya Routh -- 'Competition and Labour Law in the United Kingdom : history, theory and practice', Ewan McGaughey -- 'A solution in search of a problem? Collective Rights and the Antitrust Labour Exemption in Italy', Antonio Aliosi and Elena Gramano -- 'Competition Law and Labour Law in Germany : legitimate cartels?', Maja Beisenherz -- 'Labour Law and Competition Law under French regulation', Leticia Driguez -- 'Competition Law, cartels and collective bargaining : an Irish goodbye?', Michael Doherty -- 'The EU, Competition Law and Workers Rights', Nicola Countouris, Valerio De Stefano and Ioannis Lianos -- 'Is South American Collective Labor Law confronted by Competition Law? A preliminary approach considering existing challenges', Pablo Arellano Ortiz-- 'Conclusion : the themes of 'Labor in Competition Law", Shae McCrystal and Ewan McGaughey.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Labor laws and legislation; Antitrust law